Management of respiratory failure from tick paralysis. Issue 12 (26th November 2013) - Webster, RA; Haskins, S; Mackay, B
<x xml:space="preserve">Abstract</x> Objective The primary objective of this review is to improve the recognition and management of respiratory failure in dogs and cats treated for tick paralysis in veterinary practice. Outline We review the definitions of respiratory failure in dogs and cats, differentiating hypoxaemic lung failure and hypercapnic ventilation failure. We also identify unsustainable breathing effort, despite normal blood gas values, as a form of respiratory failure. We analyse the research into possible mechanisms of respiratory failure in dogs and cats with tick paralysis and propose strategies that may aid in identification and management of respiratory failure when it develops in small animal patients affected by tick paralysis. Conclusions Dogs and cats with tick paralysis may develop respiratory failure despite management with tick antiserum. Prompt recognition and effective support strategies should improve the survival of these patients.